2011
DOI: 10.1097/opx.0b013e31822f4d7c
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Accommodative Dysfunction in Children: Results from a Randomized Clinical Trial

Abstract: Purpose To report the effectiveness of various forms of vision therapy/orthoptics in improving accommodative amplitude and facility in children with symptomatic convergence insufficiency (CI) and co-existing accommodative dysfunction. Methods In a randomized clinical trial, 221 children 9 to 17 years with symptomatic CI were assigned to one of four treatments. Of the enrolled children, 164 (74%) had accommodative dysfunction; 63 (29%) had a decreased amplitude of accommodation with respect to age, 43 (19%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 24 publications
6
64
1
6
Order By: Relevance
“…8 Research has shown that convergence insufficiency, in particular, is responsive to targeted vision therapy. 31 Additionally, there is evidence to support the use of vision therapy for accommodative deficits, impaired version movements, and minor ocular misalignments. 8 The value of incorporating vestibular and visual rehabilitation into the management of post-concussive patients with vestibular and ocular motor impairments, as identified by the VOMS, warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…8 Research has shown that convergence insufficiency, in particular, is responsive to targeted vision therapy. 31 Additionally, there is evidence to support the use of vision therapy for accommodative deficits, impaired version movements, and minor ocular misalignments. 8 The value of incorporating vestibular and visual rehabilitation into the management of post-concussive patients with vestibular and ocular motor impairments, as identified by the VOMS, warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for our physical examination, we only obtained near-point convergence as a one-time measure; other clinics have taken the approach of averaging three separate measures. 50 …”
Section: Discussionmentioning
confidence: 99%
“…12 The ruler is placed at the center the subject’s forehead, and a measurement is taken when the patient reported the letters became double. A failed exam was defined as the letters becoming double at greater than 6 cm from the patient’s forehead.…”
Section: Methodsmentioning
confidence: 99%